Evaluation methodology to determine most influential indicators of water resources management in new cities in Egypt - NADA SALEH mohammed taher (Journal of Architecture, Art & Humanistic Science, 2023)
The development of future plans and visions for the sustainable development of new urban agglomerations in Egypt in light of the current and future challenges to face the issue of scarcity of water resources and in light of the current trend of urban development in new settlements, this calls for a statistical analysis of indicators of sustainability of development in light of this issue in order to identify and evaluate the strengths and weaknesses of water resources management With these gatherings, to find out the number of developmental directives needed by decision-makers, which help in achieving the sustainability of urban development in different dimensions, whether urban, social, economic and environmental. The research presents the most important findings of the evaluation and statistical analysis result to determine the most influential indicators to be used when setting development plans and programs through an analysis of common indicators to determine the status of water resources management in these new cities The research starts from analyzing and evaluating the current situation of water resources management in new cities by measuring development sustainability indicators that take into account the scarcity of common water resources and identifying the indicators most influential in achieving sustainable development in new cities in Egypt using the SPSS statistical program. This is in order to direct policies and decision-makers to deal with water resources in new cities in light of water scarcity to achieve sustainable development in these cities.Key words: Statistical analysis – indicator system - new cities - water scarcity -Water Resources Management (WRM) - The Egyptian Code for Water Networks.